2020
DOI: 10.3233/jad-200488
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bifidobacterium breve in Improving Cognitive Functions of Older Adults with Suspected Mild Cognitive Impairment: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Background: Probiotics use has been associated with modulation of inflammation and considered as a possible intervention for CNS diseases such as mild cognitive impairment (MCI) and dementia. Objective: We aimed to test the effect of the probiotic strain, Bifidobacterium breve A1 (MCC1274), to restore cognition in a physically healthy, suspected MCI population. Methods: In this randomized, double-blind, placebo-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 30 publications
1
113
0
2
Order By: Relevance
“…Polyunsaturated fatty acid [51] and probiotic [52] consumption have been shown to ameliorate or preserve cognitive function. Previous studies have suggested that intake of the probiotics Bi dobacterium [52] or Lactobacillus [53] inhibits cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyunsaturated fatty acid [51] and probiotic [52] consumption have been shown to ameliorate or preserve cognitive function. Previous studies have suggested that intake of the probiotics Bi dobacterium [52] or Lactobacillus [53] inhibits cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Polyunsaturated fatty acid [51] and probiotic [52] consumption have been shown to ameliorate or preserve cognitive function. Previous studies have suggested that intake of the probiotics Bi dobacterium [52] or Lactobacillus [53] inhibits cognitive decline. Dietary diversity is also protective against cognitive decline [54], and nutritional education [55] is essential for patients and their family members.…”
Section: Discussionmentioning
confidence: 99%
“…Very recent animal studies [ 306 , 307 ], clinical trials [ 308 ] and a meta-analysis of randomized controlled clinical trials [ 309 ] also suggest that altering microbiota with probiotics can lead to changes in brain function including cognitive functions. Mice in an early stage of AD were treated with a probiotic formulation, that decreased their cognitive decline compared with controls and reduced accumulation of amyloid β aggregates [ 310 ].…”
Section: Therapeutic Options/perspectives To Slow Down Cognitive mentioning
confidence: 99%
“… Kim et al (2020) reported that administrating a probiotic mixture ( Bifidobacterium bifidum BGN4 and Bifidobacterium longum BORI) promoted mental flexibility and alleviated stress in healthy older (≥ 65 years) subjects. Moreover, Bifidobacterium breve A1 (MCC1274) treatment improved memory function in healthy older adults suffering from MCI ( Xiao et al, 2020 ). The probiotic bacterium Lactobacillus rhamnosus GG improved cognitive performance in middle-aged and older adults with cognitive impairment ( Sanborn and Azcarate-Peril, 2020 ).…”
Section: Gut Microbiota Probiotics and Agingmentioning
confidence: 99%